A scenario of the scientific publication on Industry 4.0 in Brazil: A bibliometric review (Research, Society and Development, 2021)
The objective of the present study is to present the implementation of industry 4.0 in Brazil. A bibliographic survey of scientific articles and publications of institutions that study technological and industrial models was carried out to this end. The articles had as their evaluation and inclusion criteria the date of publication (2012-2019) and the language (Portuguese), focusing on the areas of Production Engineering. The articles' analysis indicates that Brazilian research points to the basis of this new industry, the internet of things, cyber-physical systems, automation, big data, and artificial intelligence as essential themes. The present study points out that the industry 4.0 model is the new and the new trend to meet an increasingly demanding, flexible, and strongly focused market for the digital age. The training of the Production Engineer must also meet these demands.